Space reconstruction of audiovisual media based on artificial intelligence and virtual reality - Zhao, Xiaoxiong; Ye, Sizhan (Journal of intelligent & fuzzy systems, 2021)
In the electronic age, the changes in the mirror space constructed by movies are also brought about by changes in the media. Cinematic space is a four-dimensional space illusion including time created by the use of light and shadow, color, perspective, sound, and the movement of characters and cameras. It is not a real four-dimensional space, but a reflection and reproduction of the real space. With the goal of improving the accuracy of spatially coded structured light 3D reconstruction, this paper conducts in-depth research on several key technologies that affect the reconstruction accuracy and makes corresponding innovations and improvements. Moreover, this paper respectively proposes an adaptive structured light spatial coding algorithm based on geometric features and a color structured light decoding algorithm based on color shift technology. In addition, this paper implements a spatially coded structured light three-dimensional reconstruction system and calibration system. The simulation research shows that the method in this paper has certain reliability.